2019
DOI: 10.1634/theoncologist.2019-0356
|View full text |Cite
|
Sign up to set email alerts
|

CIC Mutation as a Molecular Mechanism of Acquired Resistance to Combined BRAF-MEK Inhibition in Extramedullary Multiple Myeloma with Central Nervous System Involvement

Abstract: Combined MEK-BRAF inhibition is a well-established treatment strategy in BRAF-mutated cancer, most prominently in malignant melanoma with durable responses being achieved through this targeted therapy. However, a subset of patients face primary unresponsiveness despite presence of the activating mutation at position V600E, and others acquire resistance under treatment. Underlying resistance mechanisms are largely unknown, and diagnostic tests to predict tumor response to BRAF-MEK inhibitor treatment are unavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Studies have supported that these mutations are driver instead of passenger for these cells. 9,16,17 However, the conditional inactivating CIC selectively in postmitotic excitatory neurons in mouse brain using NEX-Cre results in a reduction in the number of cells expressing CUX1 and SATB2 in layer 2 of the cortex. 4 In contrast, using hematopoietic-specific deletion and bone marrow transplantation studies, the loss of Cic from hematopoietic cells results in upregulation of KRAS pathway and is sufficient to drive T cell acute lymphoblastic leukemia/lymphoma (T-ALL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have supported that these mutations are driver instead of passenger for these cells. 9,16,17 However, the conditional inactivating CIC selectively in postmitotic excitatory neurons in mouse brain using NEX-Cre results in a reduction in the number of cells expressing CUX1 and SATB2 in layer 2 of the cortex. 4 In contrast, using hematopoietic-specific deletion and bone marrow transplantation studies, the loss of Cic from hematopoietic cells results in upregulation of KRAS pathway and is sufficient to drive T cell acute lymphoblastic leukemia/lymphoma (T-ALL).…”
Section: Discussionmentioning
confidence: 99%
“…10,15 A large number of somatic variants have also been found in other non-CNS-related cancers such as lung cancer, gastric cancer, acute lymphocytic leukemia; these are not cataloged here. 6,16,17 The search of variant of CIC in gnomAD in February of 2020 has uncovered 12 loss of function variants that include seven splicing, two frameshift, and three stop-gain variants (►Supplementary Fig. S1).…”
Section: In Silico Analysis Of Cic Variant and Literature Reviewmentioning
confidence: 99%
“…It is also interesting to note that the mutational state of EGFR and the activation of the EGFR/Ras/ERK pathway associates with the central nervous system (CNS) tropism of several tumors [34][35][36][37] and that hyperstimulation of several tyrosine kinases and mitogen-activated protein kinases have been found in MM patients with aggressive disease and CNS involvement [38,39]. These patients that are usually p53 and/or BRAF mutated [40,41] show clinical response to pomalidomide [42] and could benefit from a combination of pomalidomide (or other IMiDs) and EGFR-targeted agents, such as cetuximab [43].…”
Section: Discussionmentioning
confidence: 99%
“…We need of specific diagnostic tests to predict HCC response to BRAF-MEK inhibitors. Nonetheless, novel insights suggested significant investigation in solid and hematological malignancies, with initial with promising results [42,43]. Recently, several data confirmed that different doses of TKIs determine inhibition or iper-activaction of the MAPK pathway, with opposite effects.…”
Section: Discussionmentioning
confidence: 99%